Development and implementation of a non-zero suppression system for HGCAL back-end electronics - Akgul, B.; Fedar, Y. E.; Yuksel, O.; Yuksel, F.; Erkmen, B.; Sakarya, U.; Polat, S. N. Tural; David, A.; Dauncey, P.; Shukla, R. (IOP Publishing Ltd, 2026)
In preparation for operations at the HL-LHC, the CMS Collaboration is upgrading its endcap calorimeters with a high granularity calorimeter (HGCAL). The HGCAL back-end electronics includes two Non-Zero Suppression (NZS) boards, which dynamically disable zero-suppression in designated regions of interest. This paper presents a detailed discussion of the principal components of the implemented NZS firmware and a comprehensive account of the hardware testing performed on the Serenity platform, including validation against a Python-based emulator. Each of the 48 DAQ (Data Acquisition) boards of a single endcap receives 432-bit NZS flags, which are generated non-zero-suppression control flags to disable zero suppression for designated regions of interest on the front-end sections and sent via high-speed output channels operating at 25 Gbps. The NZS firmware processes data from six EMTF input links operating at 25 Gbps, and produces the necessary non-zero suppression control flags for real-time selection and spatial mapping of up to 27 muon candidates per bunch crossing under a 360 MHz system clock constraint. To meet the stringent timing requirements, the design adopts a fully pipelined FPGA architecture, enabling deterministic latency while sustaining continuous high-throughput operation.
Keywords: Digital electronic circuits; Simulation methods and programs; Instruments & Instrumentation